Strategic Performance Measurement of MSMEs Based on ESG in Sudajaya Girang Village - Indrawan, Andri; Eriswanto, Elan; Himawan, Irfan Sophan; Rahmadini, Salva Aulia (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study aims to analyze the measurement of strategic performance of Micro, Small, and Medium Enterprises (MSMEs) using the Environmental, Social, and Governance (ESG) approach in Sudajaya Girang Village, Sukabumi Regency. MSMEs play a vital role in driving local economic growth, creating employment opportunities, and improving community welfare. However, performance measurement systems of MSMEs have largely focused on financial aspects, while sustainability dimensions have received less attention. The implementation of the ESG framework is expected to provide a more comprehensive perspective in assessing MSMEs’ performance, covering environmental responsibility, social contribution, and good governance practices. This study employs a descriptive-qualitative approach with a case study of MSMEs in Sudajaya Girang Village. Data were collected through interviews, observations, and document analysis, and analyzed using data reduction, presentation, and conclusion drawing techniques. The findings indicate that the level of understanding of ESG principles among MSME actors is varied, with implementation mostly concentrated on social and governance aspects, while environmental considerations remain limited. By applying ESG-based measurement, this study proposes a more inclusive strategic performance evaluation framework, which can serve as a guideline for developing sustainability-oriented MSMEs and supporting the achievement of the Sustainable Development Goals (SDGs).